(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article presents a comprehensive exploration of introduced amaranth medicinal plants, focusing on their morphobiological properties, innovative applications, and advancements in pest research. Amaranth species have garnered increasing attention in recent years due to their medicinal properties and nutritional value. Through a synthesis of scientific literature and research findings, this paper offers insights into the morphobiological characteristics of introduced amaranth species, including their morphology, anatomy, and physiological traits. Furthermore, the article delves into recent scientific innovations in the application of amaranth medicinal plants. From traditional medicinal uses to modern pharmacological applications, amaranth species have demonstrated promising therapeutic potential in various health conditions. The paper highlights emerging trends and breakthroughs in the field, shedding light on novel formulations, dosage forms, and therapeutic approaches. In addition to exploring the medicinal properties of introduced amaranth species, this article examines recent advancements in pest research related to amaranth cultivation. Pests pose significant challenges to amaranth production, affecting yield, quality, and sustainability.